PETROLOGY AND GEOCHEMISTRY OF THE QUATERNARY CALDERA-FORMING, PHONOLITIC GRANADILLA ERUPTION, TENERIFE (CANARY ISLANDS) - Bryan S.E. (My University, 2006)
The Granadilla eruption at 600?ka was one of the largest phonolitic explosive eruptions from the Las Canadas volcano on Tenerife, producing a classical plinian eruptive sequence of a widespread pumice fall deposit overlain by an ignimbrite. The eruption resulted in a major phase of caldera collapse that probably destroyed the shallow-level magma chamber system. Granadilla pumices contain a diverse phenocryst assemblage of alkali feldspar + biotite + sodian diopside to aegirine–augite + titanomagnetite + ilmenite + nosean/hauyne + titanite + apatite; alkali feldspar is the dominant phenocryst and biotite is the main ferromagnesian phase. Kaersutite and partially resorbed plagioclase (oligoclase to sodic andesine) are present in some eruptive units, particularly in pumice erupted during the early plinian phase, and in the Granadilla ignimbrite at the top of the sequence. Associated with the kaersutite and plagioclase are small clots of microlitic plagioclase and kaersutite interpreted as quenched blebs of tephriphonolitic magma within the phonolite pumice. The Granadilla Member has previously been recognized as an example of reverse-then-normal compositional zonation, where the zonation is primarily expressed in terms of substantial variations in trace element abundances with limited major element variation (cryptic zonation). Evidence for cryptic zonation is also provided by the chemistry of the phenocryst phases, and corresponding changes in intensive parameters (e.g. T, f?O2, f? H2O). Geothermometry estimates indicate that the main body of phonolite magma had a temperature gradient from 860?°C to ?790?°C, with hotter magma (?900?°C) tapped at the onset and terminal phases of the eruption. The reverse-then-normal chemical and thermal zonation reflects the initial tapping of a partially hybridized magma (mixing of phonolite and tephriphonolite), followed by the more sequential tapping of a zoned and relatively large body of highly evolved phonolite at a new vent and during the main plinian phase. This suggests that the different magma types within the main holding chamber could have been laterally juxtaposed, as well as in a density-stratified arrangement. Correlations between the presence of mixed phenocryst populations (i.e. presence of plagioclase and kaersutite) and coarser pumice fall layers suggest that increased eruption vigour led to the tapping of hybridized and/or less evolved magma probably from greater depths in the chamber. New oxygen isotope data for glass and mineral separates preclude syn-eruptive interaction between the vesiculating magma and hydrothermal fluids as the cause of the Sr isotope disequilibrium identified previously for the deposit. Enrichment in radiogenic Sr in the pumice glass has more likely been due to low-temperature exchange with meteoric water that was enriched in 87Sr by sea spray, which may be a common process affecting porous and glassy pyroclastic deposits on oceanic islands.
Keywords: zoned magma chamber; explosive eruption; oxygen isotopes; phonolite; plinian; Tenerife; Кайнозой::Четвертичная; Cenozoic::Quaternary